Use of the Laser Beam Deflection Technique for Thermo-Optic Coefficients Study in Gadolinium-Yttrium Oxyorthosilicate Doped with Erbium Ions - K. V. Yumashev; V. I. Goman; L. K. Pavlovski; A. V. Hertsova; A. M. Malyarevich (Приборы и методы измерений)
Results of use of the laser beam deflection technique for determination of thermo-optic coefficients (TOCs) of the Er3+-doped gadolinium-yttrium oxyorthosilicate crystal (Er3+:(GdY) SiO– Er:GYSO) are presented. A 0.1 at.% Er-doped gadolinium-yttrium oxyorthosilicate crystal was grown by the Czochralski method under nitrogen atmosphere. Raw materials such as Er2O3, Gd2O3, Y2O3, and SiO2 were weighed according to the formula (Er0.001Gd0.8995Y0.0995)2SiO5. Optical properties of the biaxial Er:GYSO crystal are described within the frame of the optical indicatrix with orthogonal principal axes Np , Nm , and Ng . To characterize the anisotropy of the TOCs a sample from the grown Er:GYSO crystal was prepared in a shape of a rectangular parallelepiped with dimensions of 7.0 (Np ) × 8.0 (Nm ) × 8.5 (Ng ) mm3. Each face of the sample is perpendicular to one of the optical indicatrix axes Np , Nm and Ng . For determination of the TOCs the laser beam deflection technique for a material with a linear temperature gradient is used. Measurements are performed at the wavelength of 632.8 nm. The thermal coefficient of the optical path (TCOP) for the Er:GYSO crystal measured at the wavelength of 632.8 nm at different light polarization E and propagation direction k were obtained. The TCOP values are positive for all directions of the light propagation k // Np , Nm , Ng . This means that the sign of the thermal lens which is directly related to the TCOP value will also be positive, and the positive thermal lens is then expected for Np Nm-, and Ng -cut Er:GYSO. Applying an analysis of the thermal lensing the dn /dT value for Yb:GYSO is estimated to be 6.5×10–6 K–1.